1997
DOI: 10.1046/j.1365-3059.1997.d01-204.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of resistance induction by Penicillum oxalicum in the biocontrol of tomato wilt

Abstract: Penicillium oxalicum, a biocontrol agent for Fusarium oxysporum f.sp. lycopersici, was tested for its ability to induce resistance against tomato wilt. P. oxalicum and F. oxysporum f.sp. lycopersici were placed at separate sites on tomato plants or in soil, avoiding a direct interaction between the fungi. P. oxalicum induced resistance as expressed by a reduction in disease severity, area under disease progress curve and stunting induced by the pathogen. P. oxalicum colonized the tomato rhizosphere during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 28 publications
5
41
0
1
Order By: Relevance
“…Reduction in severity of Fusarium wilt of tomato by P. oxalicum under greenhouse conditions was reported earlier (De Cal et al, 1995, 1997. The growth chamber experiments developed in the present study allowed us to obtain similar results of reduction of severity (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Reduction in severity of Fusarium wilt of tomato by P. oxalicum under greenhouse conditions was reported earlier (De Cal et al, 1995, 1997. The growth chamber experiments developed in the present study allowed us to obtain similar results of reduction of severity (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Regression analyses of the relative disease reduction on the percentage of disease, with data from the growth chamber experiments and with data from experiments done in greenhouses (De Cal et al, 1997) are presented in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillium oxalicum slightly inhibits M. phaseolina supported by De Cal et al (1997) identified disease reduction was observed when P. oxalicum was applied before or after inoculation with the pathogen. Penicillium chrysogenum constrains the growth of M. phaseolina (Dong et al, 2006) reported that dry mycelium of P. chrysogenum contributed to induced resistance against Verticillium dahliae in cotton.…”
mentioning
confidence: 79%
“…oxalicum has been reported to be a pathogenic fungus of the sugarcane aphid, Ceratovacuna lanigera as well as a biocontrol agent of F. oxysporum f. sp. lycopersici (De Cal et al, 1997;Santamarina et al, 2002). Its pathogenic mechanisms toward plant pathogens are derived from chitinolytic activities that degrade fungal cell wall (Rodriguez, 1993), which is also targeting PCN because one of the main chemicals composing PCN egg shell (9%) is chitin (Clarke et al, 1967).…”
Section: Discussionmentioning
confidence: 99%